Catalytic Transfer-Hydrogenation of Fatty Oil - Fitri Hadiah (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Polyunsaturated fatty acids are the main cause of the poor thermal and oxidative stabilities of fatty oils as well as biodiesels. The conversion of polyunsaturated to monounsaturated fatty acid moieties are normally carried out via hydrogenation. The most conventional hydrogenation process uses gaseous hydrogen at relatively high temperature and pressure in the presence of metal catalysts. Catalytic-transfer hydrogenation is an alternative method for oil hydrogenation which does not require the presence of hydrogen and can be carried out at atmospheric pressure. This paper describes the catalytic transfer-hydrogenation of kapok seed oil (Ceiba pentandra) and candlenut oil (Aleurites moluccana) by potassium formate (KOOCH) solutions using the following catalysts: Ag–Cu2O, Ag–Cu2O/Pumice, Ag–Cu2O–Pd/Pumice, and Pd/C 5%. None of the catalysts were found effective and kapok seed oil hydrogenated using 5%-Pd/C catalyst turned into gel, most probably due to the polymerization reactions of sterculic and malvalic acid